ROFI Zone (Region of Freshwater Influence) and Its Impact on Total Dissolved Solids in the Coastal District of Sukadana Kayong Utara - Zan Zibar; I Wayan Nurjaya; Robin Saputra; Alimuddin Alimuddin; Ferdy Gustian; Mohammad Sumiran Paputungan (Journal of Applied Geospatial Information, 2022)
Coastal areas are characterized by complex dynamics between freshwater entering through the estuary from land and seawater from open water. This study aims to calculate the salinity anomaly found on the sandy coast of Mayang, estimate the number of fractions and the volume of mass transport of fresh water entering the waters through the river flow and measure the total dissolved solids (TDS) in the west season. Water mass characteristics data collection using Water Checker. The determination of 17 data collection stations is assumed to be representative in representing the overall condition of the research location. The results of the anomaly salinity calculation show the low anomalous salinity values that are distributed horizontally on the coast. The distribution of salinity as anomaly values transversely on lines 1 to 4 ranges from -1 to -15. Freshwater fraction is concentrated as far as 1.16 km from the coast of Pasir Mayang with concentration values ranging from 0.44% to 0.13%. The mass transport of fresh water in the Pasir Mayang coastal waters is 1,130 m3s -1. The value of the transport volume of fresh water depends on rainfall and the flow of fresh water through rivers and then into sea waters. The total dissolved solids at the study site at each station ranged from 7.88 ppm to 17.8 ppm.